Markets in the name of socialism : the left-wing origins of neoliberalism - Bockman, Johanna (Stanford University Press, 2011)
The worldwide spread of neoliberalism has transformed economies, polities, and societies everywhere. Rather than focusing on the agency of a few prominent, conservative economists, this book reveals a dialogue among many economists on both sides of the Iron Curtain about democracy, socialism, and markets. These discussions led to the transformations of 1989 and, unintentionally, the rise of neoliberalism. The book takes a truly transnational look at economists' professional ideas over 100 years across the capitalist West and the socialist East.